The Role of Nutritional Access in Malnourished Elderly Undergoing Major Surgery for Acute Abdomen: A Propensity Score-Matched Analysis. Issue 8 (August 2021) - Gogna, Shekhar; Samson, David; Choi, James; Con, Jorge; Prabhakaran, Kartik; Rhee, Peter; Latifi, Rifat
Background: About 50% of the elderly undergoing emergency abdominal surgery are malnourished. The role of timely surgical nutritional access in this group of patients is unknown. Methods: We analyzed the National Inpatient Sample database from 2009 through the first three-quarters of 2015 of patients aged ≥65 years who were malnourished and underwent major abdominal surgery for the acute abdomen within the first 2 days of hospital admission. Results: Of 3 246 721 patients analyzed, 4311 patients met inclusion criteria. Of these, only 507 (11.8%) patients had surgical nutritional access (gastrostomy or jejunostomy) (group I), while 3804 patients (88.2%) did not (group II). In the propensity score-matched population, there were 482 patients in each group. The patients in group I had lower odds of mortality and postoperative gastrointestinal complications (paralytic ileus, anastomotic dehiscence, and intestinal fistulae) ( P -value <.01, respectively). Discussion: Elderly who receive surgical nutritional access have lower rates of gastrointestinal complications and mortality.